K.H. Misbah Ibn Zainul Musthafa (1916-1994 M): Pemikir dan Penulis Teks Keagamaan dari Pesantren - Islah Gusmian (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2016)
This article describes the literary tradition of pesantren in writing religious texts produced by the kiais. The case examined in this article is KH. Misbah ibn Zainul Mustafa Bangilan, the leader of Pesantren AlBalagh, Bangilan, Tuban, East Java. He has written some religious texts, both translation and original work, with a variety of approaches in defining topics, language and script, as well as writing techniques. His works show that pesantren is not only as a space for the transfer of knowledge and education of character building under the guidance of kiyais. Also, they – as shown in the figure KH. Misbah ibn Zainul Mustafa also represent sufficiently rich and comprehensive literary work in various fields of Islamic studies. In the hands of kiais, pesantren has become a scriptorium and at the same place where the kiais write Islamic religious texts and publish them, so that they can be read by the public. Keywords: Pesantren, Kiai, Manuscript, Religious Text, Islam, Java. Artikel ini menjelaskan tentang tradisi penulisan teks-teks keagama-an yang terjadi di dunia pesantren yang dilakukan oleh para kiai pesantren. Kasus yang diangkat dalam artikel ini adalah KH. Misbah ibn Zainul Mustafa Bangilan, pengasuh Pesantren Al-Balagh, Bangilan, Tuban, Jawa Timur. Dari tangannya telah lahir teks-teks keagamaan, baik terjemahan maupun asli, dengan beragam topik bahasan, bahasa dan aksara yang digunakan, serta teknik penulisan. Dari karya-karya yang dihasilkan tersebut menunjukkan bahwa pesantren bukan hanya sebagai ruang di mana transfer ilmu pengetahuan dan pendidikan karakter dilakukan oleh para kiai. Lebih dari itu, mereka—seperti tampak pada sosok KH. Misbah ibn Zainul Mustafa—juga merepresentasikan anggitan dalam berbagai bidang keilmuan Islam yang cukup kaya dan komprehensif. Di tangan kiai, pesantren menjadi skriptorium dan sekaligus tempat di mana kiai menulis teks-teks keagamaan Islam dan mempublikasikannya di tengah masyarakat, sehingga bisa dibaca oleh masyarakat luas. Kata Kunci: Pesantren, Kiai, Manuskrip, Teks Keagamaan, Islam, Jawa.